PENERAPAN MEDIA PEMBELAJARAN BERBASIS WEBSITE DINAMIS PADA PROSES PEMBELAJARAN MENULIS TEKS PUISI RAKYAT SISWA SMP KELAS VII - Wanti Wahyuni; Ika Mustika; Enung Nurhayati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Learning activities must use media that are in accordance with the character of students at the junior high school level, so that they can increase the enthusiasm of students to learn. The reality faced by junior high school students in state schools in Lembang is that students are less enthusiastic in paying attention to the material presented by the teacher. This is due to the absence of the use of images and the delivery of the dominant material using the script. This study intends to explain the impact of the application of dynamic website-based learning media on the material for writing folk poetry in seventh grade junior high school. Qualitative descriptive is the method and approach used in this research. In February 2022 this research was conducted. The data obtained in this research came from questionnaires, quizzes, and observation sheets. The output based on this research tells that, by using dynamic website media that emphasizes the principle of flexibility, it can increase the value and creativity of students in writing folk poetry texts. in writing people's poetry.